Original Article Non-Hematological Malignancies Seeding in Bone Marrow: A 6 Years’ Experience at Tertiary Care Hospital - Gahlot, Gaurav PS; Ahuja, Ankur; Baranwal, Ajay Kumar; Madhukar, Gunjan; Asthana, Bhushan; Chatterjee, Tathagata; Sahai, Kavita (Annals of Pathology and Laboratory Medicine, 2020)
Background: Bone marrow is the site of origin for primary haematological malignancies and is the third common preferred site metastasized by the solid tumors. The malignant infiltration of the hematopoietic tissue alters the clinical course of disease, response of the treatment and influences the overall survival. The aim of this study was to assess pattern of bone marrow involvement by different solid tumors and their correlation with hematological parameters. Methods: In this retrospective study, 8064 bone marrow examinations from Jan 2011-Aug 2017 at tertiary health and research centre of Northern India were evaluated to access spectrum of different solid tumors infiltrating the bone marrow alongwith their clinical, hematological and histopathological findings. Result: Total 38 cases of non-hematological malignancies metastasizing to bone marrow were evaluated with main indications of lytic lesions, cytopenia and Pyrexia of Unknown Origin. The most common metastasis were adenocarcinoma of prostate and lung. In 33 cases, the clinical, cytomorphological and immunohistochemical analysis findings were correlated to know primary site, while in remaining five patients, even after complete diagnostic evaluation, the definitive origin could not be ascertained, therefore categorized as Carcinoma of Unknown Primary Site (CUPS). Conclusion: Our series showed that anemia as commonest parameter, followed by leukopenia, thrombocytopenia. Many cases were misdiagnosed as multiple myeloma due to lytic lesion, anemia and hypercalcemia. We concluded that unexplained cytopenia are strong indicators of bone marrow examination; an easy, convenient, sensitive, effective procedure of staging of tumor, monitoring the course and prognosis of solid tumors.